Enhanced Blue Afterglow through Molecular Fusion for Bio‐applications. (5th May 2022) - Su, Xianlong; Kong, Xiaoyan; Sun, Kuangshi; Liu, Qian; Pei, Yuetian; Hu, Donghao; Xu, Ming; Feng, Wei; Li, Fuyou
Abstract: Afterglow materials have drawn considerable attention due to their attractive luminescent properties. However, their low‐efficiency luminescence in aqueous environment limits their applications in life sciences. Here, we developed a molecular fusion strategy to improve the afterglow efficiency of photochemical afterglow materials. By fusing a cache unit with an emitter, we obtained a blue afterglow system with a quantum yield up to 2.59 %. This is 162 times higher than that achieved with the traditional physical mixing system and more than an order of magnitude larger than that of the covalent coupling system. High‐efficiency afterglow nanoparticles were obtained and utilized for bio‐imaging with a high signal‐to‐noise ratio (SNR) of 131, and for the lateral flow immunoassay (LFIA) of β‐hCG with a low limit of detection (LOD) of 0.34 mIU mL −1 . This paves a new way for the construction of high‐efficiency afterglow materials and expands the number of luminescence reporter candidates for disease diagnosis and bio‐imaging. Abstract : We developed a molecular fusion strategy to achieve a high‐efficiency photochemical afterglow system. The afterglow quantum yield was up to 2.59 %, which was significantly higher than that achieved with the physical mixing strategy and the covalent coupling strategy. This afterglow system was further used for high SNR bio‐imaging and for the background‐free high‐sensitivity lateral flow immunoassay detection of β‐hCG.